Checking Consistency Between Message Choreographies And Their Implementation Models - Kozyura, Vitaly; Roth, Andreas; Wieczorek, Sebastian; Wei, Wei (Electronic Communications of the EASST, 2011)
Applying the concepts of Service-Oriented Architectures (SOA) has already become a mainstream in industry. The development of business applications according to these principles implies a layered design and implementation. This paper describes an industrial approach to the verification of a consistency relation between such layers. In our case service choreographies defined by Message Choreography Models (MCM) and their corresponding implementation models represented as Business Objects are examined. By translating both into Event-B specifications we are able to prove the consistency relation between them. A number of case studies with realistic industrial software models were carried out which showed the solidness of our verification technique. Apart from giving details about our concrete realization, this paper also discusses general challenges that have to be faced when developing a verification approach applicable for the real-world systems.